Regional and local economic development - Hague, Cliff; Hague, Euan.; Breitbach, Carrie (Basingstoke, Hampshire [England] ; New York : Palgrave Macmillan, 2011)
Containing over 70 case studies from developing and developed economies around the world, this book provides a broad introduction to regional and local economic development. It explores how government, private industry and individuals interact to achieve economic development. Discussion topics and associated readings consolidate understanding.
Includes bibliographical references and index.
Keywords: Economic development; Economic policy; Regional economics; Regional planning -- Economic aspects